Evaluating the best available social science for natural resource management decision-making. Issue 73 (July 2017) - Charnley, Susan; Carothers, Courtney; Satterfield, Terre; Levine, Arielle; Poe, Melissa R.; Norman, Karma; Donatuto, Jamie; Breslow, Sara Jo; Mascia, Michael B.; Levin, Phillip S.; Basurto, Xavier; Hicks, Christina C.; et al.
Highlights: Best available social science can improve management decisions and may be required. Best available science standards fall short for evaluating qualitative social science. We propose evaluative criteria for the full range of best available social science. The criteria have commonalities and differences with those used for natural science. Abstract: Increasing recognition of the human dimensions of natural resource management issues, and of social and ecological sustainability and resilience as being inter-related, highlights the importance of applying social science to natural resource management decision-making. Moreover, a number of laws and regulations require natural resource management agencies to consider the "best available science" (BAS) when making decisions, including social science. Yet rarely do these laws and regulations define or identify standards for BAS, and those who have tried to fill the gap have done so from the standpoint of best available natural science. This paper proposes evaluative criteria for best available social science (BASS), explaining why a broader set of criteria than those used for natural science is needed. Although the natural and social sciences share many of the same evaluative criteria for BAS, they also exhibit some differences, especially where qualitative social science is concerned. Thus we argue that the evaluative criteria for BAS should expand to include those associated with diverse social science disciplines, particularly the qualitative social sciences. We provide one example from the USA of how a federal agency − the U.S. Forest Service − has attempted to incorporate BASS in responding to its BAS mandate associated with the national forest planning process, drawing on different types of scientific information and in light of these criteria. Greater attention to including BASS in natural resource management decision-making can contribute to better, more equitable, and more defensible management decisions and policies.